Understanding Patau syndrome in India: Prevalence and clinical spectrum from a tertiary care laboratory - Ganguly, Chandrima; Banerjee, Byapti; Chatterjee, Sukanta; Kumar Saha, Ashis; Dutta, Atreyee (Indian Journal of Case Reports, 2026)
Trisomy 13, also known as Patau syndrome, is characterized by profound multisystem congenital anomalies and an exceptionally high rate of perinatal morbidity and mortality. A systematic case series was conducted involving four clinically suspected cases of Patau syndrome evaluated by the Department of Genetics at Nirnayan Healthcare, a tertiary care laboratory in Kolkata, West Bengal, between 2021 and 2026. After obtaining written informed consent,peripheral blood samples were collected, whole-blood cultures were established, and G-banded karyotyping was performed in strict accordance with International System for Human Cytogenomic Nomenclature 2020 guidelines to detect chromosomal abnormalities. Cytogenetic analysis confirmed trisomy 13 in all four cases, presenting in different cytogenetic forms: Pure trisomy with karyotypes 47,XY,+13 and 47,XX,+13; mosaic trisomy represented as 47,XY,+13[20]/46,XY[30]; and a Robertsonian translocation involving two chromosomes 13, designated as 46,XX,+13,der(13;13)(q10;q10). This case series demonstrates the cytogenetic diversity of Patau syndrome in Eastern India, including full trisomy, mosaicism, and Robertsonian translocation, underscoring the importance of accurate cytogenetic diagnosis for effective clinical management and genetic counseling. It also highlights significant gaps in access to genetic services, particularly in rural areas, leading to delayed diagnosis and increased familial burden. Expanding prenatal screening programs and integrating genetic services into public health systems are essential for early detection, informed reproductive decision-making, and improved clinical outcomes